An innovative approach to food fortification using baker’s yeast - T. V. Yuraskina; E. N. Sokolova; N. A. Fursova; E. M. Serba (Пищевые системы, 2024)
Currently, the problem of deficiency of macro- and micronutrients in the diet of the population remains relevant. One of the promising areas for solving this problem is the development of methods for the production of domestic food ingredients with the aim of creating food products fortified with microelements on their basis. The biotechnological method for production of such ingredients is considered one of the most relevant. The most widely used microorganism in the food industry is the Saccharomyces cerevisiae yeast. The aim of the research was to study the possibility of baker’s yeast enrichment with microelements: zinc and chromium. The possibility of yeast fortification during batch fermentation on malt wort with the addition of salt solutions — sources of trace elements (zinc sulfate (ZnSO4×5H2O) and chromium (III) chloride (CrCl3×6H2O)) was confirmed. The optimal dosages of the selected trace element salts for fortification were 250 mg Zn/dm3 and 500 µg Cr/dm3. An increase in the crude protein content by 11.6±0.5% was also observed. When using this combination (250 mg Zn/dm3 + 500 µg Cr/dm3), it was possible to reach optimal results in the process of simultaneous enrichment of the object with two microelements. It makes possible to obtain a sample with a concentration of 263.4±13 mg Zn/100 g of yeast (percentage of incorporation was 58.8%) and 308.2±15 µg Cr/100 g of yeast (percentage of incorporation was 34.4%). An increase in the crude protein content by 30±1.5% was also observed. The possibility of including the produced experimental samples in food products was studied. Bread as a mass consumer product was chosen as a model. Experimental bread samples were produced with a complete replacement of yeast without enrichment with yeast fortified with zinc and chromium. Organoleptic evaluation and study of important parameters such as moisture and acidity demonstrated that the experimental samples can be used in the food industry after passing the necessary safety tests. The values of replenishing the norms of physiological needs in microelements when consuming 100 g of the experimental bread samp